Impact of Chemotherapy and Radiotherapy on Management of Early Stage Clear Cell and Papillary Serous Carcinoma of the Uterus. Issue 4 (1st May 2017) - Hong, Julian C.; Foote, Jonathan; Broadwater, Gloria; Gaillard, Stéphanie; Havrilesky, Laura J.; Chino, Junzo P.
Abstract : Objective: The aim of the study was to assess interaction of lymph node dissection (LND), adjuvant chemotherapy (CT), and radiotherapy (RT) in stage I uterine papillary serous carcinoma (UPSC) and uterine clear cell carcinoma (UCC). Methods/Materials: The National Cancer Data Base was queried for women diagnosed with International Federation of Gynecology and Obstetrics stage I UPSC and UCC from 1998 to 2012. Overall survival (OS) was estimated for combinations of RT and CT by the Kaplan-Meier method stratified by histology and LND. Multivariate Cox proportional hazard models were generated. Results: Uterine papillary serous carcinoma: 5432 women with UPSC were identified. Uterine papillary serous carcinoma had the highest 5-year OS with CT + RT with (83%) or without LND (76%). On multivariate analyses, CT [hazard ratio (HR), 0.77; P = 0.01] and vaginal cuff brachytherapy (HR, 0.68; P = 0.003) with LND were independently associated with OS. Without LND, vaginal cuff brachytherapy (HR, 0.53; P = 0.03), but not CT (HR, 1.21; P = 0.92), was associated with OS. Uterine clear cell carcinoma: 2516 women with UCC were identified. Uterine clear cell carcinoma with and without LND had comparable 5-year OS for all combinations of CT and RT on univariate and multivariate analyses. Conclusions: In stage I papillary serous uterine cancer, brachytherapy and CT were associated with increased survival; however, the benefit of chemotherapy was limited to those with surgical staging. In contrast, no adjuvant therapy was associated with survival in stage I uterine clear cell carcinoma, and further investigation to identify more effective therapies is warranted.